1978
DOI: 10.1128/aac.14.4.617
|View full text |Cite
|
Sign up to set email alerts
|

New Antipseudomonal Penicillin, PC-904: Affinity to Penicillin-Binding Proteins and Inhibition of the Enzyme Cross-Linking Peptidoglycan

Abstract: The mechanism of action of a new antipseudomonal penicillin, PC-904, was studied with respect to its binding affinities to penicillin-binding proteins (PBPs) and its inhibitory activities on cross-linking enzymes of peptidoglycan synthesis in vitro. PC-904 showed especially high affinity (compared with that of penicillin G) to Escherichia coli PBP-3. It also had high affinities to PBP-2 and -1Bs and low affinities to PBP-1A, -4, -5, and -6. Similar results were obtained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…Preliminary results of research on the affinity of cefotaxime for the penicillin-binding proteins (PBPs) of P. aeruginosa (7), done by S. it is imperative, we think, that experiments similar to ours be done with many more analogs and other derivatives of cefotaxime. Conclusions from these will allow for our better understanding of the structure-versus-activity relationship that has eluded us until now.…”
Section: Discussionmentioning
confidence: 87%
“…Preliminary results of research on the affinity of cefotaxime for the penicillin-binding proteins (PBPs) of P. aeruginosa (7), done by S. it is imperative, we think, that experiments similar to ours be done with many more analogs and other derivatives of cefotaxime. Conclusions from these will allow for our better understanding of the structure-versus-activity relationship that has eluded us until now.…”
Section: Discussionmentioning
confidence: 87%
“…Noguchi and colleagues have clearly shown that the increased activity of apalcillin is due to its high affinity for penicillin-binding proteins (9,10). The discrepancy between MIC and MBC values and the inoculum effect are clearly due to the P-lactamase instability of apalcillin.…”
Section: Resultsmentioning
confidence: 99%
“…In β-lactam-treated cells of E. coli and P. aeruginosa, this change has been attributed to inhibition of PBP3 [75,119]. PBP3 crosslinks peptidoglycan at the septal wall but not the lateral wall, so inhibition of this enzyme results in cell elongation without division [58,86].…”
Section: Filamentationmentioning
confidence: 99%